Essential Oils as a Potential Neuroprotective Remedy for Age-Related Neurodegenerative Diseases: A Review - Aswir Abd Rashed; Ahmad Zuhairi Abd Rahman; Devi Nair Gunasegavan Rathi (Molecules, 2021)
Despite the improvements in life expectancy, neurodegenerative conditions have arguably become the most dreaded maladies of older people. The neuroprotective and anti-ageing potentials of essential oils (EOs) are widely evaluated around the globe. The objective of this review is to analyse the effectiveness of EOs as neuroprotective remedies among the four common age-related neurodegenerative diseases. The literature was extracted from three databases (PubMed, Web of Science and Google Scholar) between the years of 2010 to 2020 using the medical subject heading (MeSH) terms “essential oil”, crossed with “Alzheimer’s disease (AD)”, “Huntington’s disease (HD)”, “Parkinson’s disease (PD)” or “amyotrophic lateral sclerosis (ALS)”. Eighty three percent (83%) of the studies were focused on AD, while another 12% focused on PD. No classifiable study was recorded on HD or ALS. EO from Salvia officinalis has been recorded as one of the most effective acetylcholinesterase and butyrylcholinesterase inhibitors. However, only Cinnamomum sp. has been assessed for its effectiveness in both AD and PD. Our review provided useful evidence on EOs as potential neuroprotective remedies for age-related neurodegenerative diseases.